Formação de professores indígenas no Teko Arandu: reflexões sobre a formação na área de ciências da natureza - Oliveira, Manoel Garcia de (2022)
The process of training indigenous teachers in Brazil aims to reduce the shortage of these professionals in basic education in indigenous communities. The research aims to study the training proposed in the Pedagogical Project of the intercultural teaching degree course, from the perspective of the formative process of indigenous teachers at the Federal University of Grande Dourados - UFGD. The course's pedagogical project emerges from struggles, demands, dialogues, elaboration, and implementation by the indigenous Guarani/Kaiowá peoples, who constitute the majority population in the state of Mato Grosso do Sul, mainly in Dourados. The choice of the theme was delimited by the lack of studies conducted in this regard, particularly concerning natural sciences. The work is based on the assumptions of a qualitative approach, documentary analysis, and interviews. During the documentary analysis, the processes described in the PP Teko Arandu regarding the training of indigenous teachers, with an emphasis on natural sciences education, were evaluated. The interview was conducted with the coordinator of the natural sciences area of the course. The course's formative proposal seeks to constantly promote dialogue between knowledge; however, it is not clear how this is practically accomplished. It is possible to conclude that the course's proposals generally encompass those described in official documents, as well as the struggles of indigenous movements, as it is focused on the specific formative process of indigenous peoples. However, regarding the training in natural sciences, a better description of the methodological steps that should be taken during the training of indigenous teachers is still necessary. Nonetheless, the course demonstrates its importance in the process of valuing and fostering dialogue about interculturality between indigenous and non-indigenous knowledge.